Secondary bacterial flagellar system improves bacterial spreading by increasing the directional persistence of swimming - Bubendorfer, Sebastian; Koltai, Mihály; Rossmann, Florian; Sourjik, Victor; Thormann, Kai M. (Proceedings of the National Academy of Sciences of the United States of America, 2014)
As numerous bacterial species, Shewanella putrefaciens CN-32 possesses a complete secondary flagellar system. A significant subpopulation of CN-32 cells induces expression of the secondary system under planktonic conditions, resulting in formation of one, sometimes two, filaments at lateral positions in addition to the primary polar flagellum. Mutant analysis revealed that the single chemotaxis system primarily or even exclusively addresses the main polar flagellar system. Cells with secondary filaments outperformed their monopolarly flagellated counterparts in spreading on soft-agar plates and through medium-filled channels despite having lower swimming speed. While mutant cells with only polar flagella navigate by a “run-reverse-flick” mechanism resulting in effective cell realignments of about 90°, wild-type cells with secondary filaments exhibited a range of realignment angles with an average value of smaller than 90°. Mathematical modeling and computer simulations demonstrated that the smaller realignment angle of wild-type cells results in the higher directional persistence, increasing spreading efficiency both with and without a chemical gradient. Taken together, we propose that in S. putrefaciens CN-32, cell propulsion and directional switches are mainly mediated by the polar flagellar system, while the secondary filament increases the directional persistence of swimming and thus of spreading in the environment.